Clinical Efficacy of Hydroxychloroquine in Patients with COVID-19: Findings from an Observational Comparative Study in Saudi Arabia - Saleh Alghamdi; Bassant Barakat; Ilhem Berrou; Abdulhakim Alzahrani; Abdul Haseeb; Mohamed Anwar Hammad; Sirajudheen Anwar; Abdulmajeed Abdulghani A. Sindi; Hussain A. Almasmoum; Mohammad Albanghali (MDPI AG, 2021)
The aim of this study was to assess the clinical effectiveness of Hydroxychloroquine-based regimens versus standard treatment in patients with the coronavirus disease admitted in 2019 to a hospital in Saudi Arabia. A comparative observational study, using routine hospital data, was carried out in a large tertiary care hospital in Al Baha, Saudi Arabia, providing care to patients with COVID-19 between April 2019 and August 2019. Patients were categorized into two groups: the Hydroxychloroquine (HCQ) group, treated with HCQ in a dose of 400 mg twice daily on the first day, followed by 200 mg twice daily; the non HCQ group, treated with other antiviral or antibacterial treatments according to protocols recommended by the Ministry of Health (MOH) at the time. The primary outcomes were the length of hospital stay, need for admission to the intensive care unit (ICU), time in ICU, and need for mechanical ventilation. Overall survival was also assessed. 568 patients who received HCQ (treatment group) were compared with 207 patients who did not receive HCQ (control group). HCQ did not improve mortality in the treated group (7.7% vs. 7.2%). There were no significant differences in terms of duration of hospitalization, need for and time in ICU, and need for mechanical ventilation among the groups. Our study provides further evidence that HCQ treatment does not reduce mortality rates, length of hospital stay, admission and time in ICU, and need for mechanical ventilation in patients hospitalized with COVID-19.